Development of a space irradiance simulator for advanced studies and materials research. Issue 1 (1st May 2022) - Swanger, A M; Krenn, A; Youngquist, R; Gibson, T L
Abstract: A lab-scale experimental apparatus that mimics the solar-thermal environment of space has recently been developed and tested at NASA Kennedy Space Center in support of novel materials research for future space science and exploration applications. The Space Irradiance Simulator (SIRS) apparatus exposes specimens up to roughly 61 mm in diameter to a similar thermal environment that exists at distances as close as 0.4 AU from the Sun. This includes a high vacuum environment, access to a deep cryogenic background temperature with optical properties that closely imitate a blackbody, and irradiance from a broadband solar "point" source at fluxes as high as 9300 W/m 2 . Cooling is provided by a Gifford-McMahon cryocooler capable of 25 W of cooling power at 20 K, with a base temperature of 14 K. A commercially available Xenon lamp acts as the solar source, creating broadband electromagnetic radiation with a spectrum similar to that of the Sun. Light is beamed through the vacuum chamber and onto a sample suspended within the cold-mass via a flexible quartz fiber bundle in conjunction with a custom vacuum feedthrough. The system design, fabrication, and operation are discussed; and results from the initial checkout testing of the system are presented.